Answer :

(i) (2 3) 4 = 1 * 4 = 1

2 (3 4) = 2 * 1 = 1


(ii) For every a, b ϵ {1, 2, 3, 4, 5},


We have, a * b = b * a


the operation * is commutative.


(iii) (2 3) = 1


(2 3) (4 * 5) = 1 * 1 = 1


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Fill in theMathematics - Exemplar

Let f : [2, ∞) <sMathematics - Exemplar

Let f : N Mathematics - Exemplar

Fill in theMathematics - Exemplar

Let f :R →<Mathematics - Exemplar

Let f : [0, 1] <sMathematics - Exemplar

Which of the follMathematics - Exemplar